2004
DOI: 10.1021/ci0342268
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Quality and Predictiveness between 3D QSAR Models Obtained from Manual and Automated Alignment

Abstract: A set of 113 flexible cyclic urea inhibitors of human immunodeficiency virus protease (HIV-1 PR) was used to compare the quality and predictive power of CoMFA and CoMSIA models for manually or automatically aligned inhibitor set. Inhibitors that were aligned automatically with molecular docking were in agreement with information obtained from existing X-ray structures. Both alignment methods produced statistically significant CoMFA and CoMSIA models, with the best q(2) value being 0.649 and the best predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Both approaches resulted in equivalent statistical significance for every test and thus only the results of the LOO analyses are detailed below. Inhibitors of angiotensin converting enzyme 114 ACHE [11] Inhibitors of acetyl-cholinesterase 111 AI [25,29] Steroid aromatase inhibitors 78 ARB [30] Nonpeptide angiotensin II receptor antagonists 28 ATA [31] Anti-tuberculosis agents 94 BZR [11] Inhibitors of benzodiazepine receptor 163 CBRA [32] Cannabinoid CB1 receptor agonists 32 COMT [33] Inhibitors of catechol-O-methyltransferase 92 COX2 [11] Inhibitors of cyclooxygenase-2 322 DAT [34] Piperidine analogues for dopamine transporter 42 DHFR [11] Inhibitors of rat dihydrofolate reductase 397 DR [35,36] Antagonists of dopamine receptor 38 ECR [37] Binding of diacylhydrazine to ecdysone receptor 50 EDC [38] Estrogen disrupting chemicals 123 GHS [39] Growth hormone secretagogue mimics 31 GPB [11] Inhibitors of glycogen phosporylase b 66 GSK3B [40] Inhibition of Glycogen synthase kinase 3 42 HIVPR [41] Inhibitors of human immunodeficiency virus protease 113 HIVRT [42,43] Inhibition of HIV-1 reverse transcriptase 101 KOA [44] Kappa opioid antagonists 39 MX [45] Mutagenicity of mutagen X analogues 29 PDE [46] Inhibition of phosphodiesterase-IV 29 PTC [47] Phase-transfer asymmetric catalysts 40 RYR [25,48] Binding of ryanoids to the ryanodine receptor 18 STEROIDS [3,25] Binding of steroids to carrier proteins 21 TCHK [49] Inhibition of trypanosoma cruzi hexokinase 42 THERM [11] Inhibitors of thermolysin 76 THR [11] Inhibitors of thrombin 88 TP2A [50] Inhibition of topoisomerase-IIa 25 YOPH [51] Inhibitors of yersinia protein tyros...…”
Section: Resultsmentioning
confidence: 99%
“…Both approaches resulted in equivalent statistical significance for every test and thus only the results of the LOO analyses are detailed below. Inhibitors of angiotensin converting enzyme 114 ACHE [11] Inhibitors of acetyl-cholinesterase 111 AI [25,29] Steroid aromatase inhibitors 78 ARB [30] Nonpeptide angiotensin II receptor antagonists 28 ATA [31] Anti-tuberculosis agents 94 BZR [11] Inhibitors of benzodiazepine receptor 163 CBRA [32] Cannabinoid CB1 receptor agonists 32 COMT [33] Inhibitors of catechol-O-methyltransferase 92 COX2 [11] Inhibitors of cyclooxygenase-2 322 DAT [34] Piperidine analogues for dopamine transporter 42 DHFR [11] Inhibitors of rat dihydrofolate reductase 397 DR [35,36] Antagonists of dopamine receptor 38 ECR [37] Binding of diacylhydrazine to ecdysone receptor 50 EDC [38] Estrogen disrupting chemicals 123 GHS [39] Growth hormone secretagogue mimics 31 GPB [11] Inhibitors of glycogen phosporylase b 66 GSK3B [40] Inhibition of Glycogen synthase kinase 3 42 HIVPR [41] Inhibitors of human immunodeficiency virus protease 113 HIVRT [42,43] Inhibition of HIV-1 reverse transcriptase 101 KOA [44] Kappa opioid antagonists 39 MX [45] Mutagenicity of mutagen X analogues 29 PDE [46] Inhibition of phosphodiesterase-IV 29 PTC [47] Phase-transfer asymmetric catalysts 40 RYR [25,48] Binding of ryanoids to the ryanodine receptor 18 STEROIDS [3,25] Binding of steroids to carrier proteins 21 TCHK [49] Inhibition of trypanosoma cruzi hexokinase 42 THERM [11] Inhibitors of thermolysin 76 THR [11] Inhibitors of thrombin 88 TP2A [50] Inhibition of topoisomerase-IIa 25 YOPH [51] Inhibitors of yersinia protein tyros...…”
Section: Resultsmentioning
confidence: 99%
“…Tervo et al recently reported the comparison of quality and predictiveness between 3D-QSAR models obtained by manual and automated alignment methods [91]. A large series of 113 flexible cyclic urea based inhibitors divided into a training set consisting of 93 compounds were used to develop models by both the CoMFA and the CoMSIA techniques and a test set consisting of 20 compounds were used as an external set to validate the models.…”
Section: Hiv-1 Protease (Pr) As Targetmentioning
confidence: 99%
“…Debnath also studied a larger set, a total of 118 cyclic ureas [15] and found models with R 2 up to 0.97, q 2 up to 0.73, and the validation sets R 2 up to 0.64. Later, Tervo et al [16] studied almost an equally large set using both CoMFA and CoMSIA approaches. The best models they found had R 2 up to 0.95, q 2 up to 0.65, and R 2 of the validation set up to 0.75.…”
Section: Introductionmentioning
confidence: 99%